Postharvest quality of tomato fruits bagged with nonwoven fabric (TNT) (2017)
The possibility of cultivation without the use of chemical insecticides or reduction thereof, associated with the requirements of consumers has motivated growers to return to the practice of bagging fruit, but it is possible that this technique causes changes in the visual and organoleptic characteristics of fruits. The objective of this study was to evaluate possible changes in postharvest characteristics in ‘Valerin’ tomato fruits produced inside nonwoven bags (TNT) and validate the best period for bagging. The fruits came from commercial cultivation of tomato plants, located in “Ubajara”, “Ceará” State, Brazil. The experiment design used 2 × 4 factorial randomized blocks with five repetitions. The factors considered two types of insecticide use: 1-Plants treated with insecticides and 2-Plants not treated with insecticides, and four ways to bag the bunches with nonwoven fabric (TNT): T1-Bagging flower, T2-Bagging the bunches with fruits with a 1.5 cm diameter, T3-Bagging the bunches with fruits with a 3.0 cm diameter, and T4-Bunches not bagged (control). Variations in color parameters (brightness and hue angle) and firmness did not compromise the fruit quality when bagging was conducted in the flower stage (T1) or when the fruits had a 1.5 cm diameter (T2). The other parameters (titratable acidity, total soluble solids, total carotenoids, lycopene and ß-carotene) showed no change when compared to the control. Bagging the tomato bunches in the flower stage or when the fruits had a 1.5 cm diameter did not change the postharvest quality.